Effect of arousal on perception as studied through the lens of the motor correlates of sexual arousal. (2016) - Mouras, Harold
Abstract: The study of sexual arousal is at the interface of affective and social neurosciences. Recent results regarding the motor correlates of sexual arousal demonstrating an early freezing response are in perfect accordance with the GANE (glutamate amplifies noradrenergic effects) model's sustaining the double role of the arousal dimension on emotional processing.